Struthanthus ramiro-cruzii (Loranthaceae), a new species from Guerrero, Mexico - Martínez-Ambriz, Emmanuel; Saldaña, Saddan Morales; Soriano-Benítez, Jacqueline V. (Phytotaxa, 2017)
A new species of Struthanthus from the state of Guerrero, Mexico, is described and illustrated: Struthanthus ramiro-cruzii. It grows in oak and pine-oak forests, in the physiographic province of the Southern Coastal Range in the Guerrerense region. It is morphologically similar to S. deppeanus, but differs by having leaves with a subcordate to truncate base, a sessile central flower of the triad and a strongly convoluted style. A key to distinguish the new species from other species of the genus present in the state of Guerrero is included.